MENGUKUR KINERJA OPERASIONAL BMT PADA TAHUN 2010 DITINJAU DARI SEGI EFISIENSI DENGAN DATA ENVELOPMENT ANALYSIS (DEA) (Studi Kasus BMT Di Kota Semarang) - Yuningrum, Heny (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2012)
The development of Islamic banking in Semarang city was rapidly since 1997 until 2012. It is thanks to the Government support in the terms of determine Islamic banking. The Support is now more easy for movement of Islamic financial institutions. the author chose the year 2010 of this research because 2010 have been reported complete leadership of the BMT. The issue of this research is how the operational of activities BMT in Semarang city has reached the level of operational efficiency in 2010 and how the forward prospects in Semarang city for competition of BMT with the another syariah financial.The population of this research are 72 BMt and the sampling of this research are 12 BMT. The population and the sample was listed by PUSKOPSYAH. The analyze of this research using WDEA which is expected to be answer the problems occurred in the BMT.The result of this Research are 3 BMT has efficiency of 55% until 90%. There are BMT Mitra Hasanah (61,51), BMT Pasadena (62,41%) and BMT Anda (71,18%). The capital and the operational expenses of three BMT must to increase until hit a target was expected. The average of That BMT only 30% from the target. And the BMt have low efficiency (less than 55%) i.e. BMT Hudatama (29,22%, BMT Fosilatama (33,28%), BMT Tumoto Bondo (47,81%). While a third of this BMT have low efficiency from variable input i.e. capital and operational expenses and savings. There are need to upgraded from 50% until 70%. The deficiency occurs in the BMT are the proportion of unbalanced input i.e. capital and operational expenses, the number of entries maintained does not match your target market. To achieve those targets each BMT must add capital, operating expenses and savings.To answering the problemof inefficient are: the value of output that should be improved by reducing the input, if the input and output was increased, so the level to the increase f of output must be greater than the rate of increase for input, or the both of output and input was decline because the derived output should be lower than input.